A new insight into the SO2 adsorption behavior of oxidized carbon materials using model adsorbents and DFT calculations. Issue 18 (27th March 2019) - Pi, Xinxin; Sun, Fei; Gao, Jihui; Qu, Zhibin; Wang, Ani; Qie, Zhipeng; Wang, Lijie; Liu, Hui
Abstract : O-doped carbon materials have been proven to be very effective for SO2 adsorption. Abstract : Heteroatom-doped carbon materials have been proven to be very effective for gas adsorption. Herein, edge-carboxylated graphene nanoplatelets with gradient oxygen contents and consistent pore structures were used as model adsorbents to independently determine the effects of the oxygen functionalization of carbon materials on the SO2 adsorption. The OGnPs were obtained by employing a simple ball milling method using dry ice by which an oxygen content as high as 14.06 wt% could be achieved, resulting in a 20 times increase in SO2 adsorption capacity as compared to that of oxygen-free graphene nanoplatelets. Both the experiments and density functional theory calculations demonstrated that the enhanced SO2 adsorption on the oxygenated carbon surface had a physisorption nature, which provided new insights into the development of advanced carbon materials with heteroatom doping for gas molecule adsorption.